Question
Factor. \[ d^{2}-2 d-3 \]
Ask by Barrett Vargas. in the United States
Feb 02,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( d^{2} - 2d - 3 = (d + 1)(d - 3) \)
Solution
To factor the quadratic expression \( d^{2} - 2d - 3 \), follow these steps:
1. **Identify the Coefficients:**
The quadratic is in the form \( ax^{2} + bx + c \), where:
- \( a = 1 \) (coefficient of \( d^2 \))
- \( b = -2 \) (coefficient of \( d \))
- \( c = -3 \) (constant term)
2. **Find Two Numbers That Multiply to \( a \times c = 1 \times (-3) = -3 \) and Add to \( b = -2 \):**
We need two numbers, let's call them \( m \) and \( n \), such that:
\[
m \times n = -3 \quad \text{and} \quad m + n = -2
\]
The numbers \( 1 \) and \( -3 \) satisfy these conditions because:
\[
1 \times (-3) = -3 \quad \text{and} \quad 1 + (-3) = -2
\]
3. **Rewrite the Middle Term Using \( m \) and \( n \):**
Replace the middle term \( -2d \) with \( 1d - 3d \):
\[
d^{2} + 1d - 3d - 3
\]
4. **Factor by Grouping:**
- Group the first two terms and the last two terms:
\[
(d^{2} + 1d) + (-3d - 3)
\]
- Factor out the common factors from each group:
\[
d(d + 1) - 3(d + 1)
\]
- Notice that \( (d + 1) \) is a common factor:
\[
(d + 1)(d - 3)
\]
5. **Final Factored Form:**
\[
d^{2} - 2d - 3 = (d + 1)(d - 3)
\]
**Verification:**
To ensure the factoring is correct, expand the factored form:
\[
(d + 1)(d - 3) = d \cdot d + d \cdot (-3) + 1 \cdot d + 1 \cdot (-3) = d^{2} - 3d + d - 3 = d^{2} - 2d - 3
\]
The original quadratic is successfully factored as:
\[
\boxed{(d + 1)(d - 3)}
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Extra Insights
To factor the expression \( d^{2}-2d-3 \), we will find two numbers that multiply to \(-3\) (the constant term) and add to \(-2\) (the coefficient of \(d\)). Those numbers are \(-3\) and \(1\). Thus, we can write the expression as: \[ (d - 3)(d + 1) \] And there you have it! The expression \( d^{2}-2d-3 \) factors nicely into \( (d - 3)(d + 1) \). Now, let’s check the roots quickly! Setting \(d - 3 = 0\) gives \(d = 3\), and \(d + 1 = 0\) gives \(d = -1\). Those values are the solutions to the equation \(d^{2}-2d-3=0\). Happy factoring!